Analisis Keandalan Crusher pada PT. Semen Bosowa sebagai Dasar Penentuan Interval Waktu Perawatan - Muhammad Arsyad Suyuti; Baso Nasrullah; M. Ali Chandra; M. Ikram Kido (Politeknik Negeri Ujung Pandang, 2018)
Maintenance of machinery and production facilities are important things that must be done to ensurethe smooth production process. So far, PT Semen Bosowa Maros carries out regular maintenance based ontechnical instructions from machine suppliers which only show general matters without considering the actualoperating conditions. This research is aimed at planning the engine maintenance strategy of the Crusher unitbased on reliability analysis by considering the system reliability improvement target reliability. Downtime datafrom each subsystem / component is converted to time between failure data. Then the data distribution testing iscarried out to get the most appropriate distribution. Based on the data distribution parameters obtained, thereliability function of each subsystem / component can be determined so that the reliability value of eachsubsystem / component and the overall system for a certain time period can be calculated. The results showed thatthe failure or breakdown of the Crusher Unit during January 2012 - January 2014 the main causes weresubsystems / components 241.BC2 (Belt Conveyor 2), 231.BC2 (Belt Conveyor 2), 241.BC1 (Belt Conveyor 1),231 .GL1 (Grizzly Feeder Vibrating), 241.CR1 (Crusher 1) and 231.BC1 (Belt Conveyor 1) so that the allocationof reliability is focused on these subsystems / components. Next, a maintenance strategy is arranged in the form ofoptimal maintenance intervals to achieve the targeted system reliability.